Canon law and Laws of religions - NACCI, MATTEO (Prawo Kanoniczne, 2017)
This work is a conference in the Institutum Utriusque Iuris of the Pontical Lateran University that want to consider the report of Canon law and Laws of religions in the academic and scientic viewpoint. In this perspective, I focused upon the tradition of Pontical Lateran University about Laws of religions studies and the important “message” of Novo Codice Decree in order to a new “academic statute” of the Laws of religions stu- dies, in relation to Canon law, in our multicultural societies of the third millennium.